EVALUASI PEMBINAAN SUMBER DAYA APARATUR PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI KALIMANTAN TIMUR - Indra Perdana (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The objectives of the study were to describe and apply the apparatus appraisal to the Regional Development Planning Board of East Kalimantan Province with the focus of the study: work facility, work field competence, discipline of time/hours of work, discipline of deeds, quality of work produced, ability in work completion. the result of the research shows the result of evaluation to the apparatus implemented by the East Kalimantan Provincial Planning Board through several coaching instruments such as the provision of work facilities, job competence, discipline on time / working hours, work discipline, quality of work produced, can make a meaningful contribution.Keyword: evaluation, coaching, apparatus.